2020
DOI: 10.1002/oby.22786
|View full text |Cite
|
Sign up to set email alerts
|

The Mitigating Effect of Phentermine and Topiramate on Weight Regain After Roux‐en‐Y Gastric Bypass Surgery

Abstract: Objective Weight regain (WR) after Roux‐en‐Y gastric bypass surgery (RYGB) starts to occur 2 years after surgery, ultimately affecting at least 25% of patients. A limited number of studies have evaluated the impact of antiobesity medications (AOMs) on this phenomenon. Methods This study reviewed the electronic medical records of 1,196 patients who underwent RYGB between 2004 and 2015. WR was evaluated by comparing each patient’s weight during subsequent postoperative office visits to nadir weight (lowest weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…A recent retrospective analysis evaluated the effectiveness of topiramate and/or phentermine for treating post‐bariatric weight regain but was limited to RYGB patients (21). Additionally, Wharton et al (15) reported that bariatric surgery type did not statistically impact the magnitude of weight loss observed with liraglutide in 117 patients at a Canadian weight‐management center (15).…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis evaluated the effectiveness of topiramate and/or phentermine for treating post‐bariatric weight regain but was limited to RYGB patients (21). Additionally, Wharton et al (15) reported that bariatric surgery type did not statistically impact the magnitude of weight loss observed with liraglutide in 117 patients at a Canadian weight‐management center (15).…”
Section: Discussionmentioning
confidence: 99%
“…Duas pesquisas avaliaram a combinação do Topiramato com a metformina. Outras cinco avaliaram a combinação do Topiramato com a fentermina [14][15][16][17][18][19][20] ; Efeitos e segurança do uso off label do topiramato na perda de peso conforme mostrou a maioria das pesquisas analisadas, pois apenas em uma das pesquisas foi possível identificar, que a terapia combinada de Topiramato e fentermina não foi bem tolerada, em que mais da metade dos pacientes parou de tomá-lo devido aos efeitos adversos 16 .…”
Section: Resultsunclassified
“…Outra pesquisa analisou 1.196 prontuários eletrônicos de pacientes submetidos a cirurgia bariátrica entre 2004 e 2015 e mostrou que a fentermina e o Topiramato, usados individualmente ou em combinação, podem reduzir significativamente a perda de peso após cirurgia bariátrica. Não foram evidenciadas desvantagem da utilização dessas medicações 18 .…”
Section: Resultsunclassified
“…Regardless of the postoperative BMI, RYGB patients were significantly more likely to lose ≥5% of their TBW with anti-obesity medications [85]. Another study of individual and combined anti-obesity medications for WR post RYGB reported that patients who received medications achieved significantly more WL compared to those not using anti-obesity medications [86]. Additionally, there was slower overall WR in the anti-obesity medications group during long term (11 year) follow up [86].…”
Section: Pharmacologicalmentioning
confidence: 99%